Pengendalian Pencucian Senyawa Nitrat Guna Meningkatkan Produktivitas Lahan Marginal Pantai Kulon Progo DIY - Gunawan Budiyanto (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2016)
A laboratory experiment was conducted to determine the organic matter in reducing Nitrate leaching of coastal sandy soil of Kulon Progo, Yogyakarta, done from February up to August 2014. This experiment was arranged in a factorial completely randomized design. The first factor were ratio of cow dung and rice straw (1:1; 1:2 and 1:3), and the second factor were N fertilizer (urea and ZA). The result showed (a) Urea as source of N-fertilizer was more suitable to apply in coastal sandy soil and (b) Organic matter with ratio of cow dung and rice straw (1:1) was able to decrease nitrate leaching of coastal sandy soil of Kulon Progo.